Treatment Algorithms for Systemic Sclerosis According to Experts - Andreu Fernández‐Codina; Kyle M. Walker; Janet Pope (2018)
Objective There is a lack of agreement regarding treatment for many aspects of systemic sclerosis ( SS c). We undertook this study to generate SS c treatment algorithms endorsed by a high percentage of SS c experts. Methods Experts from the Scleroderma Clinical Trials Consortium and the Canadian Scleroderma Research group (n = 170) were asked whether they agreed with SS c algorithms from 2012. Two consensus rounds refined agreement; 62, 54, and 48 experts (36%, 32%, and 28%, respectively) completed the first, second, and third surveys, respectively. Results For treatment of scleroderma renal crisis, 81% of experts agreed (first‐, second‐, and third‐line treatments were angiotensin‐converting enzyme inhibitors, then adding calcium‐channel blockers [ CCB s], then adding angiotensin receptor blockers [ ARB s], respectively). For pulmonary arterial hypertension ( PAH ), 81% of experts agreed (for mild PAH , treatments were phosphodiesterase 5 [ PDE 5] inhibitors, then endothelin receptor antagonists plus PDE 5 inhibitors, then prostanoids, respectively; for severe PAH , prostanoids were first‐line treatment). For mild Raynaud's phenomenon ( RP ), 79% of experts agreed (treatments were CCB s, then adding PDE 5 inhibitors, then ARB s or switching to another CCB , respectively; after the third line of treatment, mild RP was deemed severe). For severe RP , the first‐ through fourth‐line treatments were CCB s, then adding PDE 5 inhibitors or prostanoids, then adding PDE 5 inhibitors (if not added as second‐line treatment) or prostanoids (if not added as second‐line treatment), then switching to another CCB , respectively. For active treatment of digital ulcers, 66% of experts agreed (first‐ and second‐line treatments were CCB s and PDE 5 inhibitors, respectively). For interstitial lung disease, 69% of experts agreed (for induction therapy, treatments were mycophenolate mofetil [ MMF ], intravenous cyclophosphamide [ IV CYC ], and rituximab, respectively; for maintenance, first‐line treatment was MMF ). For skin involvement, 71% of experts agreed (for a modified Rodnan skin thickness score [ MRSS ] of 24, first‐ and second‐line treatments were methotrexate [ MTX ] and MMF , respectively; for an MRSS of 32, first‐ through fourth‐line treatments were MMF , MTX , IV CYC , and hematopoietic stem cell transplantation, respectively). For inflammatory arthritis, 79% of experts agreed (first‐ through fourth‐line treatments were MTX , low‐dose glucocorticoids, hydroxychloroquine, and rituximab or tocilizumab, respectively). Algorithms for cardiac and gastrointestinal involvement had ≥75% agreement. Conclusion Total agreement for SS c algorithms was considerable. These algorithms may guide treatment.